2013
DOI: 10.5194/acp-13-3163-2013
|View full text |Cite
|
Sign up to set email alerts
|

Weak global sensitivity of cloud condensation nuclei and the aerosol indirect effect to Criegee + SO<sub>2</sub> chemistry

Abstract: Abstract. H2SO4 vapor is important for the nucleation of atmospheric aerosols and the growth of ultrafine particles to cloud condensation nuclei (CCN) sizes with important roles in the global aerosol budget and hence planetary radiative forcing. Recent studies have found that reactions of stabilized Criegee intermediates (CIs, formed from the ozonolysis of alkenes) with SO2 may be an important source of H2SO4 that has been missing from atmospheric aerosol models. For the first time in a global model, we invest… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
75
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(77 citation statements)
references
References 51 publications
2
75
0
Order By: Relevance
“…Cloudy conditions as well as enhanced oxidant concentrations in summertime could also augment sulfate production, which we show is moderately underestimated at the surface in summertime in our simulation. It has also been suggested that including reactions of stabilized Criegee intermediates with sulfur dioxide in models can produce a 10-25 % increase in sulfuric acid (H 2 SO 4 ) annually and a 100 % increase in July (Pierce et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Cloudy conditions as well as enhanced oxidant concentrations in summertime could also augment sulfate production, which we show is moderately underestimated at the surface in summertime in our simulation. It has also been suggested that including reactions of stabilized Criegee intermediates with sulfur dioxide in models can produce a 10-25 % increase in sulfuric acid (H 2 SO 4 ) annually and a 100 % increase in July (Pierce et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…This precursor could be similar to the extra SOA treated by Spracklen et al (2011) or, e.g., a fraction of some other condensable material treated in the model, as discussed above. We used the GEOS-Chem-TOMAS model (as described in Pierce et al, 2013) to study the seasonal behavior of this extra SOA and to determine if it can be used to describe our "background". As suggested by Spracklen et al (2011), 100 Tg SOA yr −1 correlated with anthropogenic CO emissions was added to the model beyond the standard biogenic SOA-precursor emissions.…”
Section: Discussion: On the Implications And Applicability Of The Parmentioning
confidence: 99%
“…Schematic of processes leading to nanoparticle growth from the perspective of the parameterization: formation of SORG MT , SORG bg and sulfuric acid from biogenic volatile organic compounds (BVOCs) and anthropogenic pollution via atmospheric oxidation and condensation of these vapors onto nanoparticles. Model simulations with GEOS-Chem-TOMAS (Pierce et al, 2013) show that SORG bg can be linked to the products of oxidation of biogenic organics in the presence of anthropogenic pollutants (Hoyle et al, 2011;Spracklen et al, 2011). particle growth. The parameterization is aimed to be simple and thus easily applicable in large-scale atmospheric models.…”
Section: S a K Häkkinen Et Al: Semi-empirical Parameterization Ofmentioning
confidence: 99%
“…Their results supported the experimental observations by Mauldin III et al (2012), showing that a signif-icant fraction (several tens of percents) of ground-level gas phase sulfuric acid originates probably from sCI-initiated oxidation of SO 2 . Pierce et al (2013) took a step further and studied the role of the sCI + SO 2 reaction to global aerosol and cloud condensation nuclei (CCN) concentrations by the global climate model. They found, in accordance with Boy et al (2013), that sCIs can contribute significantly to gas phase H 2 SO 4 in the lower troposphere above forested areas.…”
mentioning
confidence: 99%
“…However, due to further aerosol dynamical processes during particle growth to CCN sizes, the influence of sCI on sulfuric acid concentration was only feebly projected to CCN concentrations, and thus to radiative forcing. However, Pierce et al (2013) used reaction rate coefficients, including the upper limit for the sCI loss rate (decomposition and reaction with water vapour), obtained by Welz et al (2012) for CH 2 OO. Furthermore, the sCI reaction rate coefficients, including sCI loss in a reaction with water, may be strongly dependent on the sCI structure.…”
mentioning
confidence: 99%